EFEKTIFITAS PENGELOLAAN SARANA BELAJAR PENDIDIKAN KESETARAAN PKBM INSAN CENDEKIA KOTA PEKANBARU - Elizabeth A Pakpahan; Daeng Ayub; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Education is an ongoing process. The ongoing process of education is intended from infants to adults and to death, which is obtained from various sources and learning resources. Effectiveness is a way of successfully creating and utilizing resources in an effort to realize operational goals. Based on the background of the above problems, the problem to be examined is how high is the effectiveness of the management of equality education learning facilities in Pekanbaru's PKBM Insane Scholar. The benefits of adding insight are related to the effectiveness of the management of PKBM Insan Cendikia Equality Education facilities in the City of Pekanbaru as a target of non-formal education. This type of research is descriptive with a quantitative approach. The population in this study amounted to 45 people. Sampling in this study uses simple random sampling. The instrument used is a questionnaire containing 34 statements. Management effectiveness in this study is measured by indicators (1) Planning (2) Procurement (3) Inventory (4) Use (5) Maintenance (6) Elimination (7) Accountability. From the results of the study it is known that the effectiveness of the management of equality education learning facilities in PKBM Scholar Persons in Pekanbaru City is high with an average mean of 4.22. The biggest contributing indicator is the use of the mean 4.30 which is high.Key Words: Effectiveness Of Management Of Learning Facilities, Learning Citizens, PKBM